Unorthodox Transcriptional Mechanisms of Lipid-Sensing Nuclear Receptors in Macrophages: Are We Opening a New Chapter? - Czimmerer, Zsolt; Halasz, Laszlo; Nagy, Laszlo (Frontiers in Endocrinology, 2020)
Work over the past 30 years has shown that lipid-activated nuclear receptors form a bridge between metabolism and immunity integrating metabolic and inflammatory signaling in innate immune cells. Ligand-induced direct transcriptional activation and protein-protein interaction-based transrepression were identified as the most common mechanisms of liganded-nuclear receptor-mediated transcriptional regulation. However, the integration of different next-generation sequencing-based methodologies including chromatin immunoprecipitation followed by sequencing and global run-on sequencing allowed to investigate the DNA binding and ligand responsiveness of nuclear receptors at the whole-genome level. Surprisingly, these studies have raised the notion that a major portion of lipid-sensing nuclear receptor cistromes are not necessarily responsive to ligand activation. Although the biological role of the ligand insensitive portion of nuclear receptor cistromes is largely unknown, recent findings indicate that they may play roles in the organization of chromatin structure, in the regulation of transcriptional memory, and the epigenomic modification of responsiveness to other microenvironmental signals in macrophages. In this review, we will provide an overview and discuss recent advances of our understanding of lipid-activated nuclear receptor-mediated non-classical or un-orthodox actions in macrophages.